Hospitalization costs of oral cancer patients in Southeast of China: a quantile regression analysis - Xiaodan Bao; Weihai Huang; Yulan Lin; Fa Chen; Fengqiong Liu; Yu Qiu; Bin Shi; Lisong Lin; Jing Wang; Baochang He (BMC Health Services Research)
Abstract Background Scant research has systematically examined the hospitalization costs of oral cancer patients in China. Therefore, this study aims to systematically analyze the hospitalization costs and identify the factors influencing these costs among oral cancer inpatients. Methods Basic information and cost data for oral cancer patients who were admitted to the hospital for the first time between July 2015 and May 2022 were collected from one grade-A tertiary hospital in Fuzhou city of Southeastern China. Quantile regression (QR) model was used to evaluate the relationship between oral cancer patients and hospitalization costs. Results A total of 1114 patients with oral cancer were included in this study. The median (interquartile range (IQR)) of total hospitalization costs was ¥42.73 (¥22.92–¥71.41) thousand. Overall, the distribution of total hospitalization costs (discounted in accordance with the Consumer Price Index) was flat during the study period (P = 0.437). According to the QR results, oral cancer patients’ hospitalization costs were considerably affected by TNM stage, surgery, adjuvant therapy, length of stay (LOS) and tumor location. Among the above influencing factors, the highest ranking of importance was surgery, followed by TNM staging, LOS and tumor location. Conclusions This study analyzed the hospitalization costs of oral cancer patients using a large sample of data for consecutive 8 years. Study results suggests that TNM stage, surgery, adjuvant therapy, LOS and tumor location were significant factors influencing hospitalization costs. Policymakers may use these findings to develop cost-control strategies for surgical interventions or advanced-stage treatments.